If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8612=2l+2(2l-4034)
We move all terms to the left:
8612-(2l+2(2l-4034))=0
We calculate terms in parentheses: -(2l+2(2l-4034)), so:We get rid of parentheses
2l+2(2l-4034)
We multiply parentheses
2l+4l-8068
We add all the numbers together, and all the variables
6l-8068
Back to the equation:
-(6l-8068)
-6l+8068+8612=0
We add all the numbers together, and all the variables
-6l+16680=0
We move all terms containing l to the left, all other terms to the right
-6l=-16680
l=-16680/-6
l=+2780
| 5.8=s-72 | | 2.5d-11=9 | | 6/25=8/x | | 0.55x=2.6 | | 2=y/10 | | 2=y10 | | 15-15y=y | | 12x-9=5x+7 | | z/2-5=2 | | 9=-9(10+x) | | )10+2x=16 | | 3e=174 | | 12+2s=15 | | 5c+7=–3 | | 8-y/8=4 | | 3x+4(3x=28)=22 | | 180=127+(2x=41) | | 2a=3a-55 | | 5^x-1=3^3x | | 8x-9=3x+46 | | -16k=64 | | v/6-3=6 | | 412=112n | | 38=45-x | | 11=5i-9 | | 8x-4=3x+5x-4 | | 7+b/9=13 | | x/1-2=8 | | b/8-5=0 | | 3.2^x+1=6 | | -4x-6=−4x−6= | | 2x+5–5x=8 |